Exploratory study on the impact of switching to nilotinib in 18 patients with chronic myeloid leukemia in chronic phase with suboptimal response to imatinib. (January 2017) - Ailawadhi, Sikander; Akard, Luke P.; Miller, Carole B.; Jillella, Anand; DeAngelo, Daniel J.; Ericson, Solveig G.; Lin, Felice; Warsi, Ghulam; Radich, Jerald
Background: The phase II, exploratory, open-label Exploring Nilotinib BCR-ABL Effects (ENABL) study [ClinicalTrials.gov identifier: NCT00644878] assessed the impact of switching to nilotinib therapy in patients with chronic myeloid leukemia in chronic phase (CML-CP) who had a suboptimal molecular response with imatinib. Methods: Patients with CML-CP who had previously achieved a complete cytogenetic response (CCyR), but had a suboptimal molecular response, with frontline imatinib therapy ( N = 18) were assigned to receive nilotinib 300 mg twice daily. The primary endpoint was the change in BCR-ABL1 transcript levels from baseline after 12 months; rates of major molecular response (MMR) and safety were also assessed. Results: At 3 months after switching to nilotinib, 10 of 17 (59%) evaluable patients had achieved MMR. At 12 months, 9 of 12 (75%) evaluable patients had achieved MMR, and the median BCR-ABL1 level among all patients remaining in the study was 0.020% on the International Scale (IS), equivalent to a 3.7-log reduction from the standardized IS baseline (primary endpoint). Adverse events (AEs) were typically grade 1/2 and manageable with dose interruptions. A total of three patients experienced serious study drug-related AEs, including pancreatitis, bradycardia, and vertigo. No deaths were reported. Conclusions: Overall, results from this exploratory study suggest that switching to nilotinib due to suboptimal molecular response with imatinib can result in improved molecular response for patients with CML-CP.